Viroscope™: a universal solution for plant virus and viroid diagnostics using HTS and cloud-based analysis - Morgante, Verónica; Jiménez, Juan Cristóbal; Ponce, Claudio; Urrutia, Cristóbal; Vera, Fernanda; Farías, Camila; Camps de la Maza, Rocío; Caro, Valentina; Muñoz, Marco; Pollak, Bernardo (Frontiers in Microbiology, 2025)
Border biosecurity and food supply face significant global challenges due to the increasing threat of plant viruses, exacerbated by international plant trade. While high-throughput sequencing (HTS) -based virus diagnosis offers promising applications, challenges in data analysis and implementation have limited widespread adoption. Viroscope™ addresses these limitations through an advanced cloud service that leverages HTS for high-certainty virus and viroid identification. A field study was conducted on plants in post-entry quarantines using the Viroscope™ algorithm to evaluate its performance for phytosanitary diagnostics of virus and viroids. Tissue samples provided by the Chilean phytosanitary agency were processed and deep-sequenced (n = 144) using the Illumina® platform, with parallel analysis using conventional and RT-qPCR methods. The results demonstrated the enhanced detection capabilities and biological insights by Viroscope™ algorithm, even in cases of low viral abundance. From the tested plants in post-entry quarantine programs, 28.5% contained regulated and/or emergent viruses and viroids. No viral pathogens from the quarantine list were detected, in agreement with RT-qPCR results. Notably, 25% of plants harbored emergent viruses with functional evidence, highlighting potential risks undetected by traditional procedures. Comparative analysis with RT-qPCR confirmed that Viroscope™ results exhibited a high degree of correlation with current methods and furthermore, Viroscope™ was able to detect viruses in samples which yielded negative RT-qPCR results. Universally applicable across plant tissue, Viroscope™ detects all known viruses and viroids in public databases while employing innovative metrics for functional assessment. The cloud-based platform facilitates global adoption of HTS technology by phytosanitary agencies through user-friendly reports that enable rapid and informed decision-making.